Decision-making behaviour in specific combat situations in judo - Heinisch, H. D.; Büsch, D. (2011)
Fighting actions with throwing techniques are always connected to (strategic)-tactical situations. The combination of both components in technique application training (Martin et. al., 1997) must be begun as early as possible. The earlier the judoka is confronted with the integration of situational marginal conditions when learning the sequence of movements, the better he will be able to variably apply throwing techniques so that they have an impact on the competition. In this training, the undermentioned aspects have to be considered in particular: • The choice of the tactically right moment and of other situations, taking into account the opponent`s behaviour (see fig. 1) • The situation from Tori`s point of view (What do I have to do when, since it is mostly effective?)